The development of the NNBAR experiment. (1st October 2022) - Backman, F.; Barrow, J.; Beßler, Y.; Bianchi, A.; Bohm, C.; Brooijmans, G.; Calen, H.; Cederkäll, J.; Damian, J.I.M.; Dian, E.; Di Julio, D.D.; Dunne, K.; et al.
Abstract: The NNBAR experiment for the European Spallation Source will search for free neutrons converting to antineutrons with a sensitivity improvement of three orders of magnitude compared to the last such search. This paper describes progress towards a conceptual design report for NNBAR. The design of a moderator, neutron reflector, beamline, shielding and annihilation detector is reported. The simulations used form part of a model which will be used for optimisation of the experiment design and quantification of its sensitivity.